Pengaruh Proses Heat Treatment (Quenching dan Tempering) Terhadap Kekerasan dan Struktur Mikro Baja Karbon Menengah - Meyzan Andreansyah; Ratna Dewi Anjan; Viktor Naubnome (Jurnal Serambi Engineering, 2024)
Technological advances mean that steel production continues to be developed with better raw materials. Carbon steel is the one of the metals that is widely used in producing machining equipment, but it requires adjustment to the hardness and ductility properties of the steel must be heat treated to obtain properties according to its use from soft to hard. This research aims to determine the effect of cooling media in the quenching process and tempering process on hardness, tensile strength and microstructure. The variations used are variations in temperature and variations in water and oil quenching cooling media. The research method used was the experimental method, using descriptive statistical data analysis techniques, then hardness testing was carried out using the micro vickers method, tensile testing, and microstructure observation. The research result showed that the highest hardness value was at a temperature variation of 900°C for the water-cooling medium with a hardness value of 490,1 VHN. The highest average tensile strength was produced by specimens with a heating temperature of 900°C with water cooling media, namely 1051,2 N/mm2. And the result of the microstructure test shows structural changes, namely the formation of a martensite structure due to the process of heating the austenite and the cooling it quickly.